2015
DOI: 10.1515/aoa-2015-0026
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Subjective Noisiness in Hospital Lobbies

Abstract: The present study was conducted in the lobbies of 16 Taiwanese urban hospitals to establish what contributes to the degree of noisiness experienced by patients and those accompanying them. Noise level measurements were then conducted by 15 min equivalent sound pressure levels (LAeq, 15 m, dB) during daytime hours. The average LAeq itself was found to be poorly related to perceived noisiness. Levels variations were better correlated, more continual noise may actually be perceived as noisier. According to the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…Darbyshire, 34 in a study of noises in intensive care units (ICUs), reported that noise sounds with higher pitches result in higher loudness than those with lower pitches, at least with respect to loudness as quantified by ISO 532-1:2017. 33 In the previous study under consideration here, 9 the noise spectra of the 16 hospital lobbies throughout the daytime (i.e. from 9:00 a.m. to 5:00 p.m.) were very similar in terms of the shape of each octave band, and in terms of higher levels of noise occurring over the middle octave range of 250–500 Hz.…”
Section: Methodsmentioning
confidence: 60%
See 1 more Smart Citation
“…Darbyshire, 34 in a study of noises in intensive care units (ICUs), reported that noise sounds with higher pitches result in higher loudness than those with lower pitches, at least with respect to loudness as quantified by ISO 532-1:2017. 33 In the previous study under consideration here, 9 the noise spectra of the 16 hospital lobbies throughout the daytime (i.e. from 9:00 a.m. to 5:00 p.m.) were very similar in terms of the shape of each octave band, and in terms of higher levels of noise occurring over the middle octave range of 250–500 Hz.…”
Section: Methodsmentioning
confidence: 60%
“…Hence, the statistical approach and the repetitive feature technology were confirmed as useful tools to apply in detailed correlation analysis of the relationships between objective measurements and subjective evaluations of complicated noise as in my previous study. 9…”
Section: Introductionmentioning
confidence: 99%
“…Some studies consider the statistical indices most commonly employed, such as L 5 , L 10 , L 50 , L 90 , and L 95 (employed in approximately 73% of the studies), and others less common ones, such as L 1 , L 70 , L 30 , and L 33 (used in 12% of the studies). It is noteworthy that 27% of the studies also performed frequency analysis (Carvalhais et al 2015 ; Chen 2015 ; Lahav 2015 ; Ai et al 2017 ; Galindo et al 2017 ; Santos et al 2017 ; Bliefnick et al 2019 ; Loupa et al 2019 ; Hasegawa and Ryherd 2020 ). In addition, 30% performed subjective analysis with questionnaires (Chen 2015 ; Oliveira et al 2015 ; de Araújo Vieira et al 2016 ; Ai et al 2017 ; Santos et al 2017 ; Cho et al 2019 ; Wu et al 2019 ; Zijlstra et al 2019 ; Astin et al 2020 ; Tang et al 2020 ), or used reverberation time measures such as RT 30 , RT 20 (Chen 2015 ; Cho et al 2019 ), or the Speech Intelligibility Index (SII) (Bliefnick et al 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, 30% performed subjective analysis with questionnaires (Chen 2015 ; Oliveira et al 2015 ; de Araújo Vieira et al 2016 ; Ai et al 2017 ; Santos et al 2017 ; Cho et al 2019 ; Wu et al 2019 ; Zijlstra et al 2019 ; Astin et al 2020 ; Tang et al 2020 ), or used reverberation time measures such as RT 30 , RT 20 (Chen 2015 ; Cho et al 2019 ), or the Speech Intelligibility Index (SII) (Bliefnick et al 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation